Conservation of Gili Iyang, the Island with the Best Oxygen: An Ecophilosophical Perspective - Zulfah Zulfah; Margareta Rahayuningsih; Adity Marianti; Muhammad Alfan Sidik (Journal of Environmental and Science Education, 2024)
Gili Iyang Island is one of the islands in Sumenep district, Madura Indonesia, which is known as the island with best oxygen after research by Lembaga Penerbangan dan Antariksa Nasional (LAPAN) with an average oxygen level of 20.9%. In 2022, there will be research by the Faculty of Advanced and Multidisciplinary Technology, Air Langga University which states that the oxygen level on Gili Iyang Island has an oxygen level of 20.3%. As a tourist village in Sumenep district, its existence is an attraction for tourists for oxygen tourism. How can the community and local government protect this area so that it remains sustainable? This research aims to see the extent to which the conservation of Gili Iyang Island is carried out using an ecophilosophy perspective. This research was conducted using a qualitative approach through data triangulation including interviews, observation, and documentation and supported by literature studies. The research results show that the people of Gili Iyang is quite good at protecting the nature of this island. There have never been any complaints about illegal felling of trees or pollution activities that have caused oxygen levels to drop significantly. Many trees grow abundantly on this island, while people's use of motorized vehicles is still relatively normal, and the cleanliness of the island at many points is also well maintained. Even so, wise behavior towards nature as taught by ecophilosophy must continue to be socialized and intensive education given to local communities. The eco-philosophy pattern implemented by the Gili Iyang community must be maintained and improved through sustainable conservation on the island they live on.